2017
DOI: 10.1002/hep.28878
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of myeloid cells exacerbates hepatitis and induces an aberrant increase in histone H3 in mouse serum

Abstract: Tissue-resident macrophages and bone marrow (BM)-derived monocytes play a crucial role in the maintenance of tissue homeostasis; however, their contribution to recovery from acute tissue injury is not fully understood. To address this issue, we generated an acute murine liver injury model using hepatocyte-specific Cflar-deficient (Cflar Hep-low ) mice. Cellular FLICE-inhibitory protein expression was down-regulated in Cflar-deficient hepatocytes, which thereby increased susceptibility of hepatocytes to death r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…MEFs and aMoC1 cells were plated onto 96-well plates and cultured for 12 h in 10% DMEM. Cells were stimulated with mTNF (10 ng ml −1 ) in the absence or presence of BV6 (1 μM), GSK’872 (5 μM), zVAD (20 μM), or Nec-1 (20 μM) for 8 h. The values of LDH release from cells were determined by Cytotoxicity Detection Kit (Roche) as described previously 13 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEFs and aMoC1 cells were plated onto 96-well plates and cultured for 12 h in 10% DMEM. Cells were stimulated with mTNF (10 ng ml −1 ) in the absence or presence of BV6 (1 μM), GSK’872 (5 μM), zVAD (20 μM), or Nec-1 (20 μM) for 8 h. The values of LDH release from cells were determined by Cytotoxicity Detection Kit (Roche) as described previously 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, IL-33 is cleaved by caspase 3 in apoptotic cells, resulting in the inactivation of its biological activity 12 . Moreover, we recently reported that large amounts of histone H3 are released from apoptotic hepatocytes and potentially involved in the development of endothelial cell injury in the livers and lungs 13 . Together, these results suggest that DAMPs are critically involved in inflammation, immune responses, and tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolome analysis was performed as previously described (Piao et al, ). Briefly, fifty microliters of the sera from mice of the indicated genotype before or after DT treatment was used for the analysis of ionic metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA and protein levels of ATG5 were measured by RT-qPCR and western blotting, respectively. To deplete Kcs in the donor livers, clodronate liposomes (cLs) were used as before (37). Then KCs (2x10 7 cells) that were isolated from the liver tissue of AAV-ATG5-shRNA-or scramble-treated rats, were injected into recipients via the portal vein during OLT (38).…”
Section: Establishment Of the Rat Hiri Model With Atg5 Knockdown Inmentioning
confidence: 99%
“…For the IR+SA group, the donors and recipients were both intraperitoneally injected with a dose of 50 mg/kg SAHA (MedchemExpress) 12 h prior to operation, and the recipients continued to receive 50 mg/kg SAHA q12 h right from reperfusion via intra-peritoneal injection (39). For the IR+SA+CL group, cL (Encapsula NanoSciences) were injected into the donors at a dose of 4 µl/g body weight via the tail vein 48 h prior to surgery according to the manufacturer's protocol (37). Depletion of KCs were verified by using flow cytometry and immunohistochemistry, respectively.…”
Section: Experimental Groupsmentioning
confidence: 99%